Nanocellulose Modified Polyethylene Separators for Lithium Metal Batteries. Issue 21 (19th April 2018) - Pan, Ruijun; Xu, Xingxing; Sun, Rui; Wang, Zhaohui; Lindh, Jonas; Edström, Kristina; Strømme, Maria; Nyholm, Leif
Abstract: Poor cycling stability and safety concerns regarding lithium (Li) metal anodes are two major issues preventing the commercialization of high‐energy density Li metal‐based batteries. Herein, a novel tri‐layer separator design that significantly enhances the cycling stability and safety of Li metal‐based batteries is presented. A thin, thermally stable, flexible, and hydrophilic cellulose nanofiber layer, produced using a straightforward paper‐making process, is directly laminated on each side of a plasma‐treated polyethylene (PE) separator. The 2.5 µm thick, mesoporous (≈20 nm average pore size) cellulose nanofiber layer stabilizes the Li metal anodes by generating a uniform Li + flux toward the electrode through its homogenous nanochannels, leading to improved cycling stability. As the tri‐layer separator maintains its dimensional stability even at 200 °C when the internal PE layer is melted and blocks the ion transport through the separator, the separator also provides an effective thermal shutdown function. The present nanocellulose‐based tri‐layer separator design thus significantly facilitates the realization of high‐energy density Li metal‐based batteries. Abstract : The capacity decay and safety problem regarding Li metal anodes can be effectively addressed with a nanocellulose modified polyolefin separator.